CAPACITY BUILDING EFFORTS FOR VILLAGE OFFICIALS AND THE VILLAGE CONSULTATIVE BODY IN CARRYING OUT THEIR DUTIES AND FUNCTIONS IN SIMARLELAN VILLAGE, SOUTH TAPANULI: UPAYA CAPACITY BUILDING BAGI APARATUR DESA DAN BADAN PERMUSYAWARATAN DESA DALAM MENJALANKAN TUGAS DAN FUNGSI DI DESA SIMARLELAN TAPANULI SELATAN - Irma Santi Laoli; Aldri Frinaldi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The purpose of this research is to explain the efforts made to increase the ability of the village apparatus and village consultative bodies to perform their respective roles in South Tapanuli Simarlelan Village. The incapacity of the village machinery and village consultative bodies to perform their roles and responsibilities is the basis of this study. In addition to purposive sampling for informant selection and SWOT analysis for data analysis, this study employs descriptive qualitative approaches. The study was carried out in the South Tapanuli Regency's Simarlelan Village Head Office y in the Muara Batang Toru District. The findings indicated that because capacity building initiatives are only implemented by local governments with erratic timelines and do not involve the apparatus and BPD as a whole, it is possible to argue that they have not been fully and appropriately implemented in order to enhance the ability of village apparatus and BPD Simarlelan in carrying out their duties and functions.